The Effect of Animated Video Learning on ESI Triage Knowledge and Student Satisfaction of Nursing Polytechnic Health Ministry of Health Makassar - Sudirman, Andi Aridhasari; Kumboyono, Kumboyono; Suryanto, Suryanto (Syntax Corporation Indonesia, 2024)
Triage at the hospital's Emergency Room (ER) is critical for prioritizing the care of emergency patients. Triage errors can be dangerous and endanger patient safety, so nursing students should have a solid understanding of triage. This study investigates the impact of ESI triage learning media containing PowerPoint and animated films on knowledge, triage decision-making (TDM), and participant satisfaction. The research used a quantitative approach with a Quasi-Experimental pretest-posttest method involving 36 5th semester Diploma Nursing students at the Makassar Ministry of Health Polytechnic. The study was divided into two groups, experimental (animated video learning) and control (PowerPoint learning), to evaluate the effect of treatment on knowledge, triage decision-making, and student satisfaction in ESI triage learning. The results of the data analysis show a significant increase in knowledge about ESI Triage and student satisfaction after the intervention, with significant values ​​of 0.001 and 0.018, respectively (p-value < 0.05). Although there was no significant increase in Triage decision-making abilities between the groups that used animated videos and Microsoft PowerPoint (p = 0.440), the use of animated videos overall increased student responses and satisfaction. MANOVA analysis confirmed that the implementation of animated videos significantly influenced knowledge and satisfaction in students with a p-value <0.05. The use of animated videos increases student knowledge and satisfaction significantly compared to PowerPoint, although it does not affect triage decision-making.